Quality Perception in Determining the Decision to Buy Omah Oblong Jogja Products - Seppa, Yusi Irensi; Wafiqah Wardah, Sitti Syarifah (Pinisi Business Administration Review, 2026)
Product quality is an important thing when determining the choice of a product made by consumers or customers. Maintaining product quality is essential for businesses to survive in a business world full of competition. This research aims to get a clear picture of how the perception of quality in determining the purchase decision of Omah Oblong Jogja products. The research approach used is qualitative research withphenomenological research which is research that wants to provide, describe, or describe. This research was carried out at Omah Oblong Jogja. The data collection technique used in this study is by using observation (observation), structured interview techniques, and documentation which is a record of past events that can be in the form of writings, drawings, or monumental works. The source of information comes from engaged employees and consumers. Qualitative data processing methods or techniques are carried out in three stages, namely data reduction, data display and conclusioni drawing/verification. In this study, it is intended to get a clear picture of the phenomenon being studied. From this study, it can be concluded that the perception of quality can be seen from product quality, product reputation, product characteristics, and product performance in purchasing decisions. From the quality of the product, it is illustrated that Omah Oblong Yogyakarta pays great attention to the quality of the products produced and efforts to maintain product quality are carried out in several ways. From the product reputation, it is illustrated that the reputation of Omah Oblong Jogja products in the eyes of consumers is very good and customer satisfaction is high. From the characteristics of the product, it is illustrated that this product has characteristics that are easy to recognize and attractive to consumers. From the performance of the product, it is illustrated that the clothing products produced are comfortable because they are made of premium cotton, as well as a medium of expression of Yogyakarta's art and culture through its distinctive designs and motifs and can last a long time. Some of the existing research challenges or problems can still be overcome, one of which is due to the motivation of consumers to want to buy because of the quality and comfort of materials, unique designs with Yogyakarta cultural identity, affordable prices, and brand reputation.